Persepsi Kualitas Layanan Museum di Indonesia: Sebuah Studi Observasi - Alexander Joseph Ibnu Wibowo (Jurnal Manajemen Maranatha, 2015)
This study aims to explore the perceived service quality of museum in Indonesia, particularly related to its service facilities. We conduct an observation study to monitor the behavior of visitors and museum facilities. In addition, weconduct in-depth interviews with a number of visitors and museum officials. The study found that service facilities already meet the expectations of visitors, such as air conditioning, building’s architecture, garden design, and collection completeness. However, there are also facilities that do not meet the expectations of visitors, such as the lighting toilets, and tour guide. The most important contribution of this studyis a theoretical model of perceived service quality in the context of museum. Further quantitative study could be done to test the model empirically.Keywords: Perceived Service Quality, Satisfaction, Marketing, Museum, Indonesia